Osteogenesis imperfecta in incidental findings of panoramic radiographic examination: Osteogenesis imperfecta pada temuan insidental pemeriksaan radiografi panoramik - Fadhlil U.A Rahman; Muhammad Fadil Hidayat; Barunawaty Yunus; Syakriani Syahrir (Makassar Dental Journal, 2023)
Osteogenesis imperfecta is a hereditary disorder easily fractured due to a high fragility with the primary suspected pathogenesis due to disruption of type 1 collagen synthesis. Clinically, abnormalities in the teeth can also be found. The purpose of this case report is to analyze the panoramic radiographic appearance of the case of osteogenesis imperfecta. A 4-year-old boy came to Hasanuddin University Hospital complaining of mobile upper and lower teeth and a history of bone fractures. The panoramic radiographic examination showed widespread loss of bone density with the impression of brittle bone in most areas of the up-per and lower jaws accompanied by missing and migration of the permanent teeth. The suspected radiodiagnostic case was os-teogenesis imperfecta. Patients were briefed on the relationship between oral conditions and systemic diseases and referred to the pediatric department to manage the systemic condition, and antibiotics and analgesics are prescribed to reduce oral discomfort. The manifestations of osteogenesis imperfecta are decreased jaw bone density, class III malocclusion, and dentinogesis imper-fecta. In this case, migration and missing permanent teeth were also found. It is concluded that clinical examination of osteo-genesis imperfecta needs to be supported by a panoramic radiographic examination to identify the condition of hard tissue, bones, and teeth. Osteogenesis imperfecta is a hereditary disorder easily fractured due to a high fragility with the primary suspected pathogenesis due to disruption of type 1 collagen synthesis. Clinically, abnormalities in the teeth can also be found. The purpose of this case report is to analyze the panoramic radiographic appearance of the case of osteogenesis imperfecta. A 4-year-old boy came to Hasanuddin University Hospital complaining of mobile upper and lower teeth and a history of bone fractures. The panoramic radiographic examination showed widespread loss of bone density with the impression of brittle bone in most areas of the up-per and lower jaws accompanied by missing and migration of the permanent teeth. The suspected radiodiagnostic case was os-teogenesis imperfecta. Patients were briefed on the relationship between oral conditions and systemic diseases and referred to the pediatric department to manage the systemic condition, and antibiotics and analgesics are prescribed to reduce oral discomfort. The manifestations of osteogenesis imperfecta are decreased jaw bone density, class III malocclusion, and dentinogesis imper-fecta. In this case, migration and missing permanent teeth were also found. It is concluded that clinical examination of osteo-genesis imperfecta needs to be supported by a panoramic radiographic examination to identify the condition of hard tissue, bones, and teeth.